KUALITAS PAPAN PARTIKEL DARI SERAT KULIT BATANG SAGU (Metroxylon spp) DENGAN PEREKAT ALAMI ASAM SITRAT BERDASARKAN WAKTU KEMPA - Suhaimi, .; Setyawati, Dina; Nurhaida, . (Universitas Tanjungpura, 2018)
The research aimed to analyze the quality of Particleboard from Sago Fiber (Metroxylon spp) and natural citric acid adhesives based on the pressing time. The research was done in Wood Processing Laboratory of Faculty of Forestry of Tanjungpura University for the preparation of raw materials and Duta Pertiwi Nusantara (DPN) Laboratory for the manufacture and testing of samples. The materials used are sago bark fiber, citric acid adhesive and water aquades. Testing of particle board properties refers to JIS A 5908 - 2003 Type 8 standard covering physical and mechanical properties. Variations of pressure time used were 10 minutes, 15 minutes, and 20 minutes. The particle board is 30 cm x 30 cm x 1 cm forged hot with a temperature of 1600C at 25 kgf / cm2 pressure. The result of the research showed that the time of impact was significant to the density, and very significant effect on water absorption, thickness development, MOE, MOR, stickiness and screw holding strength, but no significant effect on water content. The physical properties of the particle board have tulltie JIS A 5908 - 2003 type 8 standards were density, moisture content, water absorption and thickness swelling at 15 minutes and 20 minutes. While the mechanical properties that fulfill the standard of JIS A 5908 - 2003 Type 8 is MOR at 20 minutes. The best particle board at 1600C with 20 minutes hot press time is: density 0,6084 g / cm3, moisture content 7.0987%, water absorption 64,9039%, thickness 4,1345% development, MOR 94,5187 kg / cm2.Keywords: Citric Acid, Particle Board, Particle Board Quality Of Sago Fiber, physical and mechanical properties, pressing Time.